ANALISIS KEUSANGAN DAN PRODUKTIVITAS PENGARANG MENGGUNAKAN HUKUM LOTKA PADA JURNAL KEWIRAUSAHAAN PADA TAHUN 2015 – 2019 - Rhoni Rodin; Eka Apriyani (UIN Imam Bonjol Padang, 2021)
This research was conducted to determine the level of obsolescence of a literature and determine the author's productivity with the law of lotka in the literature on entrepreneurship in 2015-2019. The research method used is quantitative research methods by conducting citation analysis. In analyzing data, data is collected, submitted, processed and then presented in tables and graphs. The result of the research is the obsolescence level of the literature with an article entitled